Diclofenac and other non-steroidal anti-inflammatory drugs (NSAIDs) are competitive antagonists of the human P2X3 receptor - Grohs, Laura; Cheng, Linhan; Cönen, Saskia; Haddad, Bassam G.; Bülow, Astrid; Toklucu, Idil; Ernst, Lisa; Körner, Jannis; Schmalzing, Günther; Lampert, Angelika; Machtens, Jan-Philipp; Hausmann, Ralf (Frontiers in Pharmacology, 2023)
The P2X3 receptor (P2X3R), an ATP-gated non-selective cation channel of the P2X receptor family, is expressed in sensory neurons and involved in nociception. P2X3R inhibition was shown to reduce chronic and neuropathic pain. In a previous screening of 2000 approved drugs, natural products and bioactive substances, various non-steroidal anti-inflammatory drugs (NSAIDs) were found to inhibit P2X3R-mediated currents. To investigate whether the inhibition of P2X receptors contributes to the analgesic effect of NSAIDs, we characterized the potency and selectivity of various NSAIDs at P2X3R and other P2XR subtypes using two-electrode voltage clamp electrophysiology. We identified diclofenac as a hP2X3R and hP2X2/3R antagonist with micromolar potency (with IC50 values of 138.2 µM and 76.7 µM, respectively). A weaker inhibition of hP2X1R, hP2X4R and hP2X7R by diclofenac was determined. Flufenamic acid (FFA) proved to inhibit hP2X3R, rP2X3R and hP2X7R (IC50 values of 221µM, 264.1µM and ~ 900µM, respectively), questioning its use as a nonselective ion channel blocker, when P2XR-mediated currents are under study. Inhibition of the hP2X3R or hP2X2/3R by diclofenac could be overcome by prolonged ATP-application or increasing concentrations of the agonist α,β-meATP, respectively, indicating competition of diclofenac and the agonists. Molecular dynamics simulation showed that diclofenac largely overlaps with ATP bound to the open state of the hP2X3R. Our results suggest a competitive antagonism through which diclofenac, by interacting with residues of the ATP-binding site, left flipper, and dorsal fin domains inhibits gating of P2X3R by conformational fixation of the left flipper and dorsal fin domains. In summary, we demonstrate the inhibition of the human P2X3 receptor by various NSAIDs. Diclofenac proved to be the most effective antagonist with a strong inhibition of hP2X3R and hP2X2/3R and a weaker inhibition of hP2X1R, hP2X4R and hP2X7R. Considering their involvement in nociception, inhibition of hP2X3R and hP2X2/3R by micromolar concentrations of diclofenac, which are rarely reached in the therapeutic range, may play a minor role for analgesia compared to the high-potency COX inhibition, but may explain the known side effect of taste disturbances caused by diclofenac.